IMPLEMENTASI HARGA, KUALITAS PELAYANAN DAN PEMBELIAN BERULANG PADA PENJUALAN PRODUK GAMIS AFIFATHIN - Enny Istanti; Bramastyo Kusumo; Indah Noviandari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
This study aims to determine the effect of prices, service quality, and repeat purchases on product sale decisions simultaneously, partialy, and significantly. And to determine which variables have a dominant influence. Methods of research using quantitative methods in the study population are consumers Gamis Afifathin Surabaya. The sampling technique used was simple random sampling and accidental sampling with a sample size of 95 respondents to the formula Slovin. Technique uses multiple linier regression analysis. The variable is the prices, service quality, repeat purchases, product sale. Result were obtained value of F count 41,563 with a significance of 0,000, t value of each variable of prices 1,094 > 1,98638, variable service quality 10,757 > 1,98638, and variable repeat purchases 0,437 > 1,98638 Based on the result of research in Product Gamis Afifathin Surabaya to the simultaneous effect of three independent variables, partial and significant impact on Product sale. The Independent variable of Service Quality has a dominant influence on the Product Sale which has a Beta value of 0,597.